2016
DOI: 10.1111/jvp.12324
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and local tolerance of cefovecin sodium after intra‐articular administration in horses

Abstract: Searching for new therapeutic options against septic arthritis in horses, this research was focused on the study of the kinetics and local side effects after the intra-articular treatment of horses with cefovecin sodium. A single dose (240 mg) of the drug (Convenia ) was administered into the radiocarpal joint of adult healthy horses (n = 6), and drug concentrations in plasma and synovial fluid were determined by high-performance liquid chromatography (HPLC). Local tolerance was also studied based on the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…43 Finally, both tobramycin and cefovecin sodium (dosed at 240 mg in the radiocarpal joint in both studies) induced mild chemical synovitis evidenced by increased nucleated cell counts and total protein in synovial fluid, although it was concluded that no clinically relevant joint damage occurred. 39,44 The long-term effects of antibiotic-induced synovitis have not been evaluated at this time to the authors' knowledge, and therefore it is unknown to what extent IA antibiotic usage may contribute to the long-term progression of osteoarthritis within the injected joint (Table 2).…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…43 Finally, both tobramycin and cefovecin sodium (dosed at 240 mg in the radiocarpal joint in both studies) induced mild chemical synovitis evidenced by increased nucleated cell counts and total protein in synovial fluid, although it was concluded that no clinically relevant joint damage occurred. 39,44 The long-term effects of antibiotic-induced synovitis have not been evaluated at this time to the authors' knowledge, and therefore it is unknown to what extent IA antibiotic usage may contribute to the long-term progression of osteoarthritis within the injected joint (Table 2).…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Pharmacokinetic distribution of antibiotics following IA injection has been explored for aminoglycosides, ceftiofur sodium and cefovecin sodium. 20,39,40,[44][45][46] When the IA route of administration was compared with regional limb perfusion, gentamicin (one gram injected by either route) reached higher peak concentrations in synovial fluid following IA injection, but did not differ in serum or bone. 45 Amikacin concentrations were lower and distribution of amikacin (500 mg) from radiocarpal joints occurred more rapidly (48 vs 72 hours) from endotoxin-inflamed vs normal joints.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Some information about cefovecin's pharmacokinetic (PK) profile is available for some non-human primates, 5-7 hens, 8 alpacas, 9 some aquatic species, 10-12 other non-domesticated species [13][14][15] and some limited information is available for the horse. 16,17 Cefovecin has a long elimination half-life in the cat and dog (≈ 7 and 5 days, respectively); 3,4 furthermore a single SC injection of 8 mg/kg body weight reportedly has antimicrobial activity in plasma and transudates between 10 and 14 days in these species. 3,4 The long elimination half-life of cefovecin has been attributed to the high proportion of plasma protein binding (PPB) in dogs, cats and monkeys (> 90%).…”
Section: Abstract Cephalosporin;mentioning
confidence: 99%